The bad peace and the good war. Rhetoric of duplicity in Augustine, from “De Civitate Dei” to "Epistola 185" - CORNEA, Ileana (Studia Universitatis Babeș-Bolyai Philosophia, 2024)
The present paper is rooted in an older concern, regarding Augustine’s contradictions[1]. In the history of ideas there is a common place that authors contradict themselves and that their ideas migrate from one pole to another. This paper aims to present the case study regarding Augustine’s contradictions. I propose to focus on an issue that interfered later with the Church’s politics, namely the subject of peace and war, as we find them in De Civitate Dei and Epistola 185. Even though the issue of peace and war appears in several of his writings, those mentioned before seem more relevant for the topic, as they were also approached previously by other authors. I equally propose to highlight that Augustine echoes some ideas on war that can be read under Plato’s pen, although he was more of a Plotinus’s follower. But, as a personal touch, I would try to incorporate it within the entire dual thought of Augustine, that was echoed in the following centuries in the thought of the scholastics and the policy of The Catholic Church. [1] I’m aiming to speak about the ideological contradictions in the present article (the good peace/the bad peace, the good war/the bad war, connected to the good love/the bad love etc)